Comparative Study of Surface Modification Treatment for Porous Titanium - Reiko Kobatake; Kazuya Doi; Yoshifumi Oki; Yusuke Makihara; Hanako Umehara; Takayasu Kubo; Kazuhiro Tsuga (eJournal of Oral Maxillofacial Research, 2020)
Objectives: This study was to investigate suitable surface treatment methods for porous titanium by ex vivo study of material properties and calcium phosphate deposition in simulated body fluid.